Penerapan Sikap Afektif Peserta Didik Dalam Pembelajaran Bahasa Indonesia Di Sekolah Dasar - Muhammad Singgih (Al Banin : Jurnal Ilmiah Pendidikan Dasar, 2023)
Measurement of affective aspects (attitudes) especially ordinary scientific attitudes is done through the scale of attitudes. However, the arrangement of attitude scales as instruments of measuring individual attitudes or group attitudes is not easy. The purpose of this study is to see the effectiveness of Media Development Against Affective Attitudes of Students In Learning Indonesian This research is expected to encourage students to follow learning well. In addition, this research can be a reference for educators and various parties in increasing the quality of teaching by applying media as an aid in learning. The type of research that will be used in field research (field research) that is qualitative descriptive is a study that describes an event or phenomenon as is so that it is in accordance with its purpose. Qualitative research methods are research methods carried out under natural conditions without being made up in line with theory, where the researcher is as a key instrument, data collection techniques are triangulated, data analysis is inductive / qualitative, and qualitative research results emphasize meaning rather than generalization. Learning can save time, because the content of lessons presented thematically can be prepared at once and given in two or three meetings, the rest of the time can be used for remedial activities, stabilization, or enrichment.